Biomimetic Trachea Regeneration Using a Modular Ring Strategy Based on Poly(Sebacoyl Diglyceride)/Polycaprolactone for Segmental Trachea Defect Repair. (23rd August 2020) - Xu, Yong; Guo, Yifan; Li, Yaqiang; Huo, Yingying; She, Yunlang; Li, Hao; Jia, Zihao; Jiang, Gening; Zhou, Guangdong; You, Zhengwei; Duan, Liang
Abstract: The lack of a biomimetic tracheal substitute featured with cartilage ring/vascularized connective tissue alternate structure (CVCAS) has significantly retarded a clinical breakthrough of tissue‐engineered trachea in repairing extensive tracheal lesions. Herein, a novel modular strategy based on cartilage rings and biomaterial rings is used to generate a biomimetic trachea with CVCAS. Poly(sebacoyl diglyceride) and polycaprolactone (PCL) (PSeD/PCL) are blended to fabricate a porous scaffold with satisfactory mechanical properties, biodegradability, and biocompatibility. A cartilage ring is engineered in vitro using ring‐shaped PSeD/PCL scaffold loaded with chondrocytes and cartilage tube is generated in vivo through the fusion of multiple modular cartilage rings. More importantly, biomimetic tracheas with CVCAS are successfully fabricated in vivo through alternately stacked cartilage rings and PSeD/PCL rings on a silicon tube. Notably, the engineered biomimetic trachea exhibits not only a bionic structure but also superior mechanical properties compared with the native rabbit trachea. Finally, segmental tracheal defects in rabbits are repaired by transplanting the biomimetic trachea with pedicled muscular flaps. The biomimetic trachea establishes stable blood supply and provided sufficient mechanical strength and biological function similar to those of native trachea. This work represents the first successful regeneration of biomimetic trachea with CVCAS and a promising approach for clinical application. Abstract : A novel modular strategy based on cartilage rings and biomaterial rings is used to generate a biomimetic trachea with a cartilage ring/vascularized connective tissue alternate structure. The cartilage ring is engineered in vitro using a ring‐shaped poly(sebacoyl diglyceride)/polycaprolactone (PSeD/PCL) scaffold. Furthermore, the biomimetic trachea is fabricated in vivo through alternately stacked cartilage rings and PSeD/PCL rings. Finally, segmental tracheal defects in rabbits are successfully repaired by the biomimetic trachea.